Pengaruh Penapatan Manfaat Dan KemudahanTerhadap Minat Penggunaan Shopee Paylater Pada Mahasiswa Unisma Fakultas Ekonomi Dan Bisnis 2020 - Rohmah, Dikri Minatur; Priyono, Achmad Agus; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The aim of this research is to determine the effect of income benefits and convenience on interest in using Shopee PayLater among students at the Faculty of Economics and Business at the Islamic University of Malang class of 2020. And the sample used in this research consisted of 80 students. The data collection technique for this research uses a questionnaire and the data analysis method used is multiple linear regression analysis. The results of this research show that. The results of this research show that income benefits and convenience have a significant effect on interest in using Shopee Paylater among students at the Islamic University of Malang, Faculty of Economics and Business, class of 2020.Keywords: Income Benefits And Ease Of Use Interest